2014
DOI: 10.1016/j.canlet.2014.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Fufang Kushen injection inhibits sarcoma growth and tumor-induced hyperalgesia via TRPV1 signaling pathways

Abstract: Cancer pain is a deleterious consequence of tumor growth and related inflammation. Opioids and antiinflammatory drugs provide first line treatment for cancer pain, but both are limited by side effects. Fufang Kushen injection (FKI) is GMP produced, traditional Chinese medicine used alone or with chemotherapy to reduce cancer-associated pain. FKI limited mouse sarcoma growth both in vivo and in vitro, in part, by reducing the phosphorylation of ERK and AKT kinases and BAD. FKI inhibited TRPV1 mediated capsaicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…CKI inhibited TRPV1-mediated capsaicin-induced ERK phosphorylation and reduced tumorinduced pro-inflammatory cytokine production ( Figure 1). Thus, CKI limited cancer pain both directly by blocking TRPV1 signaling and indirectly by reducing tumor growth [29] . The efficacy of CKI has been evaluated in cancer patients either alone or in conjunction with chemotherapeutic or radiotherapeutic treatments.…”
Section: Studies On Compound Kushen Injectionmentioning
confidence: 99%
“…CKI inhibited TRPV1-mediated capsaicin-induced ERK phosphorylation and reduced tumorinduced pro-inflammatory cytokine production ( Figure 1). Thus, CKI limited cancer pain both directly by blocking TRPV1 signaling and indirectly by reducing tumor growth [29] . The efficacy of CKI has been evaluated in cancer patients either alone or in conjunction with chemotherapeutic or radiotherapeutic treatments.…”
Section: Studies On Compound Kushen Injectionmentioning
confidence: 99%
“…Previous studies have shown that PI3K/Akt and ERK1/2 activation contributes to the development of cancer pain (Han et al, 2012;Zhao et al, 2014;Wang et.al, 2011;Wang et al, 2012aWang et al, , 2012b. Furthermore, a recent study showed that TRPV1 could also mediate ERK phosphorylation and tumor-induced pro-inflammatory cytokine production in cancer pain (Zhao et al, 2014).…”
Section: Crosstalk Between Pi3k/akt and Raf/mek/erk Pathwaysmentioning
confidence: 96%
“…Previous studies have shown that PI3K/Akt and ERK1/2 activation contributes to the development of cancer pain (Han et al, 2012;Zhao et al, 2014;Wang et.al, 2011;Wang et al, 2012aWang et al, , 2012b. Furthermore, a recent study showed that TRPV1 could also mediate ERK phosphorylation and tumor-induced pro-inflammatory cytokine production in cancer pain (Zhao et al, 2014). The discovery of the ubiquitous crosstalk between PI3K/Akt and Raf/MEK/ERK pathways by Guan et al indicates that the interaction between CXCR3 and other receptors, such as TRPV1, may exist in the mechanism of BCP, and these also raise the question of how the phosphorylation of Akt and ERK1/2 mechanistically leads to chronic nociceptive behavior.…”
Section: Crosstalk Between Pi3k/akt and Raf/mek/erk Pathwaysmentioning
confidence: 99%
“…Fufang Kushen injection, a traditional Chinese medicine, was approved by the China FDA in 1995 for treatment of nonsmall-cell lung cancer, liver cancer and gastric cancer [3][4][5]. It has been widely used for the treatment of diverse cancer patients in combination with other anticancer drugs, such as vinorelbine, cisplatin and taxol.…”
mentioning
confidence: 99%
“…It is a dynamic process Our previous studies demonstrated that tricyclic sophoridinic derivatives showed a potent antitumor activity via inhibiting the DNA topoisomerase I activity, inducing cell-cycle arrest at the G0/G1 phase, and cause apoptotic cell death in tumor cells, similar to that of parent sophoridine [4][5][6]. However, little is known about the ability of this kind of compounds to affect autophagy in tumor cells.…”
mentioning
confidence: 99%